Sex Differences in Cardiovascular Risk Associated With Long-Term PM2.5 Exposure: A Systematic Review and Meta-Analysis of Cohort Studies - Zhang, Jia; Wang, Xinyan; Yan, Mengfan; Shan, Anqi; Wang, Chao; Yang, Xueli; Tang, Naijun (Frontiers in Public Health, 2022)
Background Established evidence suggests risks of developing cardiovascular disease are different by sex. However, it remains unclear whether associations of PM2.5 with cardiovascular risk are comparable between women and men. The meta-analysis aimed to examine sex differences in associations of ischemic heart disease (IHD) and stroke with long-term PM2.5 exposure. Methods PubMed, EMBASE and Cochrane Library were searched until May 2, 2021. We included cohort studies reporting sex-specific associations of long-term PM2.5 exposure (e.g., ≥1 year) with IHD and stroke. The primary analysis was to estimate relative risk (RR) of PM2.5-outcome in women and men separately, and the additional women-to-men ratio of RR (RRR) was explored to compare sex differences, using random-effect models. Results We identified 25 eligible studies with 3.6 million IHD and 1.3 million stroke cases among 63.7 million participants. A higher level of PM2.5 exposure was significantly associated with increased risk of IHD in both women (RR = 1.21; 95% CI, 1.15–1.27) and men (RR = 1.12; 95% CI, 1.07–1.17). The women-to-men RRR of IHD was 1.05 (95% CI, 1.02–1.08) per 10 μg/m3 increment in PM2.5 exposure, indicating significant excess risk of IHD in women. The significant risks of stroke associated with PM2.5 were obtained in both women (RR = 1.11; 95% CI, 1.08–1.13) and men (RR = 1.11; 95% CI, 1.07–1.14), but no significant women-to-men RRR was observed in stroke (RRR = 1.00; 95% CI, 0.96–1.04). Conclusions The study identified excess risk of IHD associated with long-term PM2.5 exposure in women. The findings would not only have repercussions on efforts to precisely evaluate the burden of IHD attributable to PM2.5, but would also provide novel clues for cardiovascular risk prevention accounting for sex-based differences.